2014
DOI: 10.1002/jso.23780
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative radiotherapy is associated with improved survival among patients with synovial sarcoma: A SEER analysis

Abstract: Background and Methods We examined the outcomes of synovial sarcoma (SS) patients in a national database. We identified 1,189 patients from the Surveillance, Epidemiology, and End Results (SEER) database with data on site and extent of surgery. We excluded patients diagnosed before 1990, <18 years, or lacking pathologic confirmation. Using Kaplan-Meier and Cox proportional hazards analyses, we determined predictors of overall (OS) and disease-specific survival (DSS). Results The mean age was 41, 49.3% were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 33 publications
6
36
0
Order By: Relevance
“…They observed an improvement in 3-y survival for patients with high-grade tumors receiving RT compared with those not receiving RT (73% versus 63%, P < 0.001). Not surprisingly, given the overlap in study patients, our results reinforce the findings of previous studies such as those of Koshy et al ., specifically the positive effects of RT, as well as female sex, married marital status, and later years of diagnosis on improved oncologic outcome [10,22]. Furthermore, similar to prior studies, we identified tumor size and grade to be strong predictors of worse oncologic outcome [5,6,20].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…They observed an improvement in 3-y survival for patients with high-grade tumors receiving RT compared with those not receiving RT (73% versus 63%, P < 0.001). Not surprisingly, given the overlap in study patients, our results reinforce the findings of previous studies such as those of Koshy et al ., specifically the positive effects of RT, as well as female sex, married marital status, and later years of diagnosis on improved oncologic outcome [10,22]. Furthermore, similar to prior studies, we identified tumor size and grade to be strong predictors of worse oncologic outcome [5,6,20].…”
Section: Discussionsupporting
confidence: 81%
“…Although previous studies have evaluated the impact of RT on OS and DSS in the multimodality management of various STS, the results have been equivocal [3,6,811,22,23]. Although there is clear benefit of RT on improved local control, some studies have demonstrated improved survival with RT, whereas randomized prospective trials by Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with adjuvant chemotherapy, fewer reports have focused on adjuvant radiotherapy in SS patients. Using the Surveillance, Epidemiology, and End Results database, Naing et al showed that adjuvant radiotherapy improved OS in SS patients. Song et al reported that adjuvant radiotherapy improved LRFS but did not affect OS in patients with localized SS.…”
Section: Discussionmentioning
confidence: 99%
“…Although radiotherapy has failed to show effect on survival in randomized controlled trials in heterogeneous soft tissue sarcoma populations, some retrospective studies reporting specifically on synovial sarcoma have identified adjuvant radiation as associated with better outcome. Song et al reported that adjuvant radiation was associated with improved progression free survival within their institution, and Naing et al identified an association between perioperative radiotherapy and prolonged disease‐specific survival in SEER. In the current study, adjuvant radiation was associated with prolonged OS in the overall cohort and among stage III patients specifically.…”
Section: Discussionmentioning
confidence: 99%